Empowering Through Group Exercise: Beat It Trainers’ Views on Successful Implementation of a Diabetes Management Program Online and In-Person - Morwenna Kirwan; Christine L. Chiu; Connie Henson; Thomas Laing; Jonathon Fermanis; Leah Scott; Jordan Janszen; Kylie Gwynne (Diabetology)
Background: The Beat It program is a clinician-led, community-based group exercise intervention for adults with Type 2 Diabetes Mellitus (T2DM). While previous studies have demonstrated its effectiveness in improving physical and mental health outcomes, this study explores the perspectives of Beat It Trainers to identify key factors contributing to the program’s success and areas for improvement. Methods: Semi-structured interviews were conducted with 11 Accredited Exercise Physiologists who had delivered both in-person and online versions of the program. Interviews were thematically analyzed using inductive approaches. Results: Eight main themes emerged: customization to individual needs, capability building, outcome improvement, affordability, accessibility, sustainability, and a holistic approach delivered in a group setting. Challenges identified included managing group dynamics, maintaining participant commitment in a fully subsidized program, and providing nutrition advice within the trainers’ scope of practice. The program’s adaptability to both in-person and online delivery modes was highlighted as enhancing its accessibility and resilience. Conclusions: This study provides valuable insights into the factors contributing to the success of the Beat It program from the implementers’ perspective. The findings suggest that investing in comprehensive training for facilitators, particularly in group dynamics management, could benefit similar programs. While the program’s fully subsidized structure reduces financial barriers to entry, innovative strategies to enhance participant engagement and perceived value should be explored. The success of the online delivery mode indicates that hybrid models offering both in-person and virtual options could increase accessibility in future supervised, community-based exercise programs for T2DM management.